2020
DOI: 10.3390/atmos11090899
|View full text |Cite
|
Sign up to set email alerts
|

Flow Regimes and Föhn Types Characterize the Local Climate of Southern Patagonia

Abstract: The local climate in Southern Patagonia is strongly influenced by the interaction between the topography and persistent westerlies, which can generate föhn events, dry and warm downslope winds. The upstream flow regime influences different föhn types which dictate the lee-side atmospheric response regarding the strength, spatial extent and phenomenology. We use a combination of observations from four automatic weather stations (AWSs) and high-resolution numerical modeling with the Weather Research and Forecast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 80 publications
(159 reference statements)
0
16
0
Order By: Relevance
“…There might thus be a different response of glaciers situated at the western and eastern sides of the Main Divide during the same large‐scale conditions, as recognized earlier by Purdie et al. (2011) for Franz Joseph and Tasman glaciers and found for other foehn‐affected glacier environments as well (e.g., Temme et al., 2020).…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…There might thus be a different response of glaciers situated at the western and eastern sides of the Main Divide during the same large‐scale conditions, as recognized earlier by Purdie et al. (2011) for Franz Joseph and Tasman glaciers and found for other foehn‐affected glacier environments as well (e.g., Temme et al., 2020).…”
Section: Discussionmentioning
confidence: 73%
“…A partitioning of the total U error into u‐ and v‐components showed that the largest overestimations by WRF coincide with very high v‐winds, suggesting that localized, terrain‐induced flow features like flow reversal and/or downslope acceleration may have produced peaks that do not align with observations. Both wind speed overestimation and cold temperature biases in WRF are frequently reported phenomena, particularly with respect to locations situated in remote regions or within complex terrain (e.g., Gómez‐Navarro et al., 2015; Temme et al., 2020; Zhang et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations